2021
DOI: 10.1037/cbs0000257
|View full text |Cite
|
Sign up to set email alerts
|

Determining the appropriateness of extended time accommodations in standardized cognitive ability testing.

Abstract: In selection contexts that employ standardized testing, the use of accommodations must be accompanied by evidence to support their appropriateness. Three studies examined the appropriateness of extended time accommodations in cognitive ability testing. Study 1 examined the speededness of the Canadian Forces Aptitude Test (CFAT) using data from 12,555 applicants to establish that speed is not a factor in the CFAT. Study 2 examined the impact of extra time in the completion of a paper-based administration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…Using an experimental design, researchers compared the test performance of students with and without disabilities under two groups: those receiving ETA and those not receiving ETA. Some studies identified differential boost (Alster, 1997; Lesaux et al, 2006); some found that ETA benefits students with LDs and SWODs equally (Furlano et al, 2021; Hjärne, 2020; Sireci et al, 2005); and others found that ETA benefits SWODs more than students with LDs (Lewandowski et al, 2013; May & Stone, 2014). A meta-analysis of findings from nine studies found that ETA is associated with improved test scores for both students with LDs and their SWODs peers who were age 14 or older (Gregg & Nelson, 2012).…”
Section: Evaluating Etamentioning
confidence: 99%
See 1 more Smart Citation
“…Using an experimental design, researchers compared the test performance of students with and without disabilities under two groups: those receiving ETA and those not receiving ETA. Some studies identified differential boost (Alster, 1997; Lesaux et al, 2006); some found that ETA benefits students with LDs and SWODs equally (Furlano et al, 2021; Hjärne, 2020; Sireci et al, 2005); and others found that ETA benefits SWODs more than students with LDs (Lewandowski et al, 2013; May & Stone, 2014). A meta-analysis of findings from nine studies found that ETA is associated with improved test scores for both students with LDs and their SWODs peers who were age 14 or older (Gregg & Nelson, 2012).…”
Section: Evaluating Etamentioning
confidence: 99%
“…It permits them to use accommodations when their disabilities or language skills unduly impact their performance and invalidate their scores (Individuals with Disabilities Education Improvement Act, 2004). The goal of test accommodations is to increase the reliability, validity, and fairness of the scores by removing construct-irrelevant measurement errors (American Educational Research Association, American Psychological Association, & National Council on Measurement in Education [AERA, APA, & NCME], 2014; Furlano et al, 2021). Test accommodations allow SWDs to demonstrate their ability and knowledge in an area and to create equal opportunities for SWDs (Elliott & Marquart, 2004; Lovett, 2010).…”
mentioning
confidence: 99%